Species Composition, Diversity, and Habitat Association of Medium- and Large-Sized Mammals in Chimit-Kolla, Abay Gorge, Ethiopia - Mengistu Wale; Mesele Yihune (International Journal of Zoology)
Identifying the species distribution, diversity, and habitat association provides input to launch proper conservation interventions. A survey of medium- and large-sized mammal species was conducted in Chimit-Kolla area to assess their distribution, diversity, and relative abundance in November 2019 to September 2020. Line transect sampling and focus group discussions were used for data collection. Shannon diversity index and Sorenson’s coefficient were used to compute the diversity and habitat utilization of species. The association of species among habitats was tested using the chi-squared test. In the survey, 18 species of medium- and large-sized mammals belonging to the order Artiodactyla (7 species), Carnivora (6 species), Rodentia (1 species), Primates (3 species) and Tubulidentata (1 species) were recorded. The association of mammalian species among the three habitats was not significant (p>0.05). However, the abundance of mammal species was significantly associated with forest habitats (p<0.05). There was a significant variation in abundance of medium- and large-sized mammal species observed in the dry season (157, 57.5%) as compared to the wet season (116, 42.5%) (χ2 = 6.17, df = 1, and p=0.013). The most abundant species was olive baboon (Papio anubis), followed by grivet monkey (Chlorocebus aethiops) and crested porcupine (Hystrix cristata). While leopard (Panthera pardus), white-tailed mongoose (Ichneumia albicauda), and aardvark (Orycteropus afer) were the rarest mammalian species recorded. Forest habitat has the highest species diversity (H’ = 2.276) than riverine vegetation and wooded grassland. Mammal species showed a considerable similarity among habitats, and the highest similarity was recorded between forest and wooded grassland (S = 0.8). The study area relatively has considerable numbers of medium- and large-sized mammal species, and urgent conservation action is required to reduce the emerging threats (hunting, charcoal production, agriculture, and investment expansion) and ensure survival of mammal species.